Annals of Intensive Care - Teboul, Jean-Louis
Annals of Intensive Care is an online peer-reviewed journal aimed at publishing high-quality review articles and original research papers on intensive care medicine. It is intended for all critical care providers (attending physicians, fellows, residents, nurses, and physiotherapists) seeking to update their own knowledge to ensure they provide the best care for their patients.